Essays in the economics of digital transformation - Moritz Goldbeck (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2024)
This dissertation consists of four essays in the economics of digital transformation and specifically considers the link between geography and digitalization in the know-ledge economy. – – Die Dissertation besteht aus vier Aufsätzen zur Ökonomie der digitalen Transformation und beleuchtet insbesondere das Zusammenwirken von Geografie und Digitalisierung in der Wissensökonomie.
Keywords: H40; J24; J30; J61; L17; L84; L86; O18; O30; O31; O33; O36; R11; R32; 330; digitization; software; knowledge work; culture; language; ICT; development; nighttime light; Africa; growth; cybercafé; geography; networks; knowledge economy; colocation; digital platforms; signaling; open source; job search